Upacara Songkran dalam Perspektif Etika, Kajian Terhadap Masyarakat Siam di Provensi Yala, Thailand Selatan. - , Saudi Tayeh, Dr. Ali Mudhofir ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study entitled Songkran Ceremony in Ethical Perspective, a Study AboutSiam Community, inthe Province of Yala, South Thailand. This research based on the community concern facing changing attitudes in Siam society, which are the influence of globalization and the moral decadence in the Praâ that clearly affect the general behavior. The aim of this study is to find both of an ethical meaning contained in Songkran ceremonies at Siam society in Yala, South Thailand, and the relevance of the ethics of Songkran ceremonies for the development of the Siamese people's behavior in Yala, South Thailand. This study is a library research which is supported by data taken from the field. Formal object of this research is ethics.Material object is the Songkran ceremony at Siam Society in the Province of Yala, South Thailand. The methods used is the historical continuity, hermeneutics, and heuristics. The results of this study are (1) revealing the ethical values and ethical obligation contained in Songkran ceremonies